A Rare Case of Aseptic Meningitis Linked to Borrelia afzelii Seroconversion in Northeastern Greece - Kouroupis, Dimitrios; Terzaki, Maria; Moscha, Nikoletta; Sarvani, Anastasia; Simoulidou, Elisavet; Chatzimichailidou, Sofia; Giza, Evangelia; Sapouridis, Georgios; Angelakis, Emmanouil; Petidis, Konstantinos; Pyrpasopoulou, Athina (Recent Updates in Disease and Health Research Vol. 6, 2024)
We describe an interesting case of probable Lyme disease with atypical features in a geographical region of Northern Greece, in which the emergence of Borreliosis is anticipated, but not established to date, and discuss on one hand the significance of maintaining a high clinical suspicion on a changing planet and, on the other, the difficulties establishing such a diagnosis. Lyme disease is an infectious syndrome caused by various species of Borrelia, a genus of bacteria of the spirochete phylum. The zoonosis known as Lyme disease, or Borreliosis is spreading around the world and is transmitted to humans and small mammals by certain tick vectors. It is linked to a range of clinical symptoms and has the potential to cause severe disability if neglected and not properly diagnosed. Borrelia burgdorferi s.s., Borrelia afzelii, Borrelia garinii, and Borrelia spielmanii are the primary Borrelia species that infect humans in Europe. The Ixodes ricinus tick is their principal vector. Although Lyme disease is considered endemic in the Balkan region and Turkey, and all three main Lyme pathogens have been detected in ticks collected in these countries, autochthonous Lyme disease remains controversial in Greece. We report a case of a 21-year-old female patient from Thasos Island in Northeastern Greece who was referred to the Emergency Department with a progressively worsening headache of 14 days duration and intermittent low-grade fever. The patient presented with fever and severe headache, and the cerebrospinal fluid examination showed lymphocytic pleocytosis. Serum analysis was positive for specific IgG antibodies against Borrelia afzelii. For a diagnosis to be made when characteristic erythema migrans are absent, serological evidence of infection is necessary. The seasonality and geographic location of possible disease transmission in the reported patient, despite the patient's unique clinical presentation, should alert clinicians to a new infectious disease in Greece that is still contentious and may be underreported.